Simulation for Authentic Learning in Informal Education - Dupuis, Jason (J Mus Educ, 2016)
In 2011, the Museum of Science and Industry in Chicago, Illinois embarked on the creation of a program that allows middle and high school students to explore community health issues using human patient simulation. MedLab was created to engage students in an authentic exploration of medical science, biology, and human anatomy, with a particular focus on how these fields apply to learners’ lives. The program content is made relevant through an emphasis on personal health, community health, and medical science career pathways. This article explores the development, implementation, use of technology, and outcomes of MedLab.